Immunohistochemical detection of Listeria ivanovii in formalin fixed paraffin embedded tissue sections - ASRANI, R K; SADANA, J R; CHAND, P; KHATRI, M (The Indian Journal of Animal Sciences, 2014)
Listeria ivanovii was successfully demonstrated in formalin fixed paraffin-embedded tissues of placenta from aborted guinea-pigs using indirect immuhoperoxidase technique. Intense reddish-brown deposits of organisms were seen in the central portion of suppurative/pyogenic granulomae, in and around the walls of thrombosed vessels and all along the. chorionic plate immediately below the surface trophoblast layer. The presence of bacteria in these locations was also demonstrated by staining of the sections with indirect immunofluorescent and Taylor’s method. The results of immunoperoxidase were better than immunofluorescent technique for the demonstration of Listeria ivanovii.